Assessing different anthropometric indices and their optimal cutoffs for prediction of type 2 diabetes and impaired fasting glucose in Asians: The Jinchang Cohort Study. Issue 5 (2nd December 2019) - Ding, Jie; Chen, Xiaoliang; Bao, Kaifang; Yang, Jingli; Liu, Nian; Huang, Wenya; Huang, Peiyao; Huang, Junjun; Jiang, Nan; Cao, Jianing; Cheng, Ning; Wang, Minzhen; et al.
Abstract: Background: To study the association between anthropometric measurements and the risk of diabetes and impaired fasting glucose (IFG) and compare body mass index (BMI), waist circumference (WC), and waist‐to‐height ratio (WHtR) to determine the best indicator and its optimal cutoffs for predicting type 2 diabetes and IFG. Methods: A Chinese prospective (2011‐2019) cohort named the Jingchang cohort that included 48 001 participants was studied. Using Cox proportional hazard models, hazard ratios (HRs) for incident type 2 diabetes or IFG per 1 SD change in BMI, WC, and WHtR were calculated. Area under the curve (AUC) was compared to identify the best anthropometric variable and its optimal cutoff for predicting diabetes. Results: The association of BMI, WC, and WHtR with type 2 diabetes or IFG risk was positive in the univariate and multivariable‐adjusted Cox proportional hazard models. Of all three indexes, the AUC of BMI was largest and that of WC was smallest. The derived cutoff values for BMI, WC, and WHtR were 24.6 kg/m 2, 89.5 cm, and 0.52 in men and 23.4 kg/m 2, 76.5 cm, and 0.47 in women for predicting diabetes, respectively. The derived cutoff values for BMI, WC, and WHtR were 23.4 kg/m 2, 87.5 cm, and 0.50 in men and 22.5 kg/m 2, 76.5 cm, and 0.47 in women for predicting IFG, respectively. [Correction added on 14 April 2020, after first online publication: '0' has been deleted from 'WC, 0' in the first sentence.]. Conclusions: Our derived cutoff points were lower than the values specified in the most current Asian diabetes guidelines. We recommend a cutoff point for BMI in Asians of 23 kg/m 2 and for WC a cutoff point of 89 cm in men and 77 cm in women to define high‐risk groups for type 2 diabetes; screening should be considered for these populations. Abstract : Highlights We observed significant and positive associations of the risk of type 2 diabetes with BMI, WC and WHtR, and we identified BMI as the best obesity predictor for diabetes. Our derived cutoff points were lower than the values specified in the most current Asian diabetes guidelines, and we recommend a cutoff point for BMI in Asians of 23 kg/m 2 and a cutoff point for WC of 89 cm in men and 77 cm in women to define high‐risk groups for type 2 diabetes; screening should be considered for these populations. 摘要: 背景: 研究人体测量指标与糖尿病和空腹血糖受损(IFG)发生风险之间的关系, 并比较体重指数(BMI)、腰围(WC)和腰高比(WHtR), 以确定预测2型糖尿病和IFG的最佳指标及其最佳截断值。 方法: 金昌队列是一项中国的前瞻性队列(2011‐2019), 其中包括48001名参与者。本研究利用COX比例风险模型, 计算BMI、WC和WHtR每变化1SD的2型糖尿病或IFG风险比(HR), 比较ROC曲线下面积(AUC), 确定预测糖尿病的最佳人体测量指标及其最佳截断值。 结果: 在单因素和多因素调整的COX比例风险模型中, BMI、WC和WHtR与2型糖尿病或IFG的发病风险呈正相关。在这三个指标中, BMI的AUC最大, WC的AUC最小。男性预测糖尿病的BMI、WC和WHtR的截断值分别为24.6kg/m 2 、89.5cm和0.52, 女性截断值分别为23.4kg/m 2 、76.5cm和0.47。男性预测IFG的BMI、WC和WHtR的截断值分别为23.4kg/m 2 、87.5cm和0.50, 女性截断值为22.5kg/m 2 、76.5cm和0.47。 结论: 本研究结果的截断值低于目前亚洲糖尿病指南中规定的数值, 我们建议亚洲人BMI的截断值为23 kg/m 2, WC的截断值为男性89cm, 女性77 cm, 以确定2型糖尿病的高危人群, 并应考虑对这些人群进行糖尿病筛查。